Fireproof elevator roller material and preparation process thereof

CN122958845APending Publication Date: 2026-10-23RUIAN ZHANPENG MACHINERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611219327.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]本申请的目的在于提供一种防火电梯滚轮材料及其制备工艺,可以改善浇注成型过程中阻燃填料受重力作用发生沉降,造成防火电梯滚轮材料径向阻燃组分分布不均,无法同步匹配高阻燃等级与材料力学性能的问题

Benefits of technology

[0015]第二方面,本申请提供一种防火电梯滚轮材料,所述防火电梯滚轮材料由第一方面任一项所述的防火电梯滚轮材料制备工艺制备得到。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958845A_ABST
    Figure CN122958845A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of elevator roller materials, and provides a fireproof elevator roller material and a preparation process thereof, and the process comprises the following steps: adding a first flame-retardant functional unit and polyurethane prepolymer into a reaction kettle, mixing under first dispersion conditions, and obtaining premixed slurry; adding a second flame-retardant functional unit into the premixed slurry, mixing under second dispersion conditions, chemically reacting first active groups carried by a surface modification layer of the first flame-retardant functional unit with second active groups carried by a surface modification layer of the second flame-retardant functional unit, forming a covalent bridging structure between the first flame-retardant functional unit and the second flame-retardant functional unit, and obtaining modified composite slurry; adding a curing agent into the modified composite slurry, sequentially performing defoaming, casting forming and post-curing treatment, and obtaining the fireproof elevator roller material. The application improves the problem that the flame-retardant filler is subjected to gravity and is settled during the casting forming process, and causes uneven distribution of the radial flame-retardant components of the fireproof elevator roller material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of elevator roller material technology, and in particular relates to a fireproof elevator roller material and its preparation process. Background Technology

[0002] Elevator door rollers are indispensable moving components of elevator door systems. They are integrally assembled at the elevator landing door mounting plate, relying on the rolling cooperation between the rollers and the door head guide rails to smoothly open and close the elevator doors. Fire-resistant elevator rollers used in firefighter elevators and fire-resistant landing doors need to maintain normal rolling ability even under high-temperature fire conditions to prevent the rollers from melting and jamming, thus preventing the elevator doors from opening and closing. Currently, commercially available fire-resistant elevator rollers generally use cast polyurethane elastomer as the molding base material. By adding halogen-free flame-retardant fillers to the cast polyurethane elastomer, the fire-resistant elevator roller material acquires flame-retardant properties. Melamine polyphosphate and aluminum diethylphosphinate are widely used nitrogen-phosphorus synergistic halogen-free flame-retardant filler combinations in this field. The synergistic effect of these two types of fillers enhances the high-temperature flame-retardant ability of the cast polyurethane elastomer.

[0003] However, in the existing technology for preparing fireproof elevator roller materials using cast-type polyurethane elastomers compounded with halogen-free flame-retardant fillers, the density of the halogen-free flame-retardant fillers is much greater than that of the liquid polyurethane prepolymer matrix, and there is a lack of stable interaction forces and spatial constraint structures between the halogen-free flame-retardant fillers. During the static period after the slurry is dispersed and poured into the mold but before gel solidification, there is no external shear constraint, and the halogen-free flame-retardant fillers settle under gravity, resulting in a radial concentration gradient distribution of flame-retardant components in the cured fireproof elevator roller material. To achieve the UL94 V-0 flame retardant rating, a high amount of halogen-free flame-retardant filler needs to be added to the polyurethane prepolymer matrix during preparation. However, a high filling ratio of halogen-free flame-retardant filler exacerbates the negative effects of powder settling, ultimately leading to insufficient surface flame-retardant component content and excessive internal flame-retardant component aggregation in the fireproof elevator roller material. For a long time, the industry has struggled to consistently achieve high-level flame retardant requirements for fireproof elevator roller materials while meeting their mechanical performance requirements. Summary of the Invention

[0004] The purpose of this application is to provide a fireproof elevator roller material and its preparation process, which can improve the problem that the flame-retardant filler settles under gravity during the casting process, resulting in uneven radial flame-retardant component distribution in the fireproof elevator roller material and the inability to simultaneously match high flame retardant rating and material mechanical properties.

[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows: In a first aspect, this application provides a process for preparing fireproof elevator roller materials, applied to a fireproof elevator roller material preparation system, the fireproof elevator roller material preparation system including a reaction vessel, the process including: The first flame-retardant functional unit and the polyurethane prepolymer are added to the reactor and mixed under the first dispersion condition to obtain a premixed slurry; the first flame-retardant functional unit is a submicron flame-retardant filler modified with a silane coupling agent. A second flame-retardant functional unit is added to the premixed slurry, and the mixture is carried out under a second dispersion condition. The first active group carried on the surface modification layer of the first flame-retardant functional unit reacts chemically with the second active group carried on the surface modification layer of the second flame-retardant functional unit to form a covalent bridging structure between the first flame-retardant functional unit and the second flame-retardant functional unit, thereby obtaining a modified composite slurry. The second flame-retardant functional unit is a micron-sized flame-retardant filler modified with a silane coupling agent. A curing agent is added to the modified composite slurry, and the mixture is then subjected to degassing, casting, and post-curing treatments to obtain a fireproof elevator roller material.

[0006] The fire-resistant elevator roller material preparation process provided in this application involves adding a first flame-retardant functional unit and a polyurethane prepolymer to a reaction vessel and mixing them under a first dispersion condition to obtain a premixed slurry. This process achieves initial uniform dispersion of submicron-level flame-retardant fillers within the polyurethane prepolymer, reducing the agglomeration and clumping of the submicron-level flame-retardant fillers. This provides a uniform and stable liquid-phase reaction substrate for the subsequent uniform chemical reaction between the first and second flame-retardant functional units. The second flame-retardant functional unit is then added to the premixed slurry and mixed under a second dispersion condition. The first active group carried by the surface modification layer of the first flame-retardant functional unit reacts chemically with the second active group carried by the surface modification layer of the second flame-retardant functional unit, further enhancing the chemical reaction between the first and second flame-retardant functional units. A covalent bridging structure is formed between the functional units to obtain a modified composite slurry. It can form a covalent connection network structure based on two types of flame-retardant functional units with different particle sizes. The free migration behavior of the flame-retardant filler inside the system is restrained by the covalent connection network structure, and the gravity settling behavior of the flame-retardant filler during the static stage of the liquid slurry is suppressed from the molding source. A curing agent is added to the modified composite slurry, and degassing, casting molding and post-curing treatment are carried out in sequence to obtain fireproof elevator roller material. It can complete the curing molding of the modified composite slurry, so that the covalent connection network structure of the flame-retardant functional units is permanently retained in the interior of the cured fireproof elevator roller material matrix. At the same time, the degassing treatment can remove the air bubble defects inside the fireproof elevator roller material, and meet the overall structural density and basic mechanical properties of the fireproof elevator roller material.

[0007] The manufacturing process of this fireproof elevator roller material effectively reduces the radial flame-retardant component concentration gradient defect caused by the settling of flame-retardant fillers during the casting process by constructing a covalently linked network structure of flame-retardant functional units through a two-stage step-by-step mixing method. It can meet the UL94V-0 flame-retardant standard without excessively increasing the total amount of flame-retardant fillers to compensate for settling losses, while simultaneously taking into account the high flame-retardant performance and long-term mechanical performance of the fireproof elevator roller material.

[0008] In some embodiments, the curing agent is 3,3'-dichloro-4,4'-diaminodiphenylmethane; the amount of the curing agent is determined according to the isocyanate content of the polyurethane prepolymer. The molar ratio was determined to be between 0.85 and 0.95.

[0009] In some embodiments, the fireproof elevator roller material preparation system includes a wet stirring mill; the preparation method of the first flame-retardant functional unit includes: Melamine polyphosphate and zirconia grinding beads with a diameter of 0.3 mm to 0.5 mm are added to the wet stirred mill at a mass ratio of 1:8 to 1:12. Deionized water is used as the grinding medium, and the mill is circulated and ground at a speed of 2000 rpm to 3000 rpm for 8 h to 16 h to obtain a grinding slurry. The median particle size D50 of the melamine polyphosphate in the grinding slurry after grinding is less than or equal to 500 nm, and the particle size D90 is less than or equal to 800 nm. γ-glycidyl etheroxypropyltrimethoxysilane is added to the grinding slurry at 1% to 3% of the mass of the melamine polyphosphate, and the mixture is stirred and reacted at 60°C to 80°C for 2 to 4 hours. The material after the reaction is completed is then spray-dried to obtain the first flame-retardant functional unit.

[0010] In some embodiments, the first flame-retardant functional unit is a submicron-sized melamine polyphosphate modified with γ-glycidoxypropyltrimethoxysilane, the median particle size D50 of the first flame-retardant functional unit is 200 nm to 500 nm, and the modification mass of the γ-glycidoxypropyltrimethoxysilane is 1% to 3% of the mass of the submicron-sized melamine polyphosphate; the second flame-retardant functional unit is a micron-sized aluminum diethylphosphinate modified with γ-aminopropyltriethoxysilane, the median particle size D50 of the second flame-retardant functional unit is 3 μm to 8 μm, and the modification mass of the γ-aminopropyltriethoxysilane is 0.5% to 1.5% of the mass of the micron-sized aluminum diethylphosphinate.

[0011] In some embodiments, the reactor includes a dispersion plate; the first dispersion conditions are a processing temperature of 50°C to 80°C, a stirring speed of 500 rpm to 800 rpm for the dispersion plate, and a mixing time of 15 min to 30 min; the second dispersion conditions are a processing temperature of 80°C to 100°C, a stirring speed of 800 rpm to 1200 rpm for the dispersion plate, and a mixing time of 20 min to 40 min.

[0012] In some embodiments, the reactor is provided with a stirring shaft, and the stirring shaft is equipped with a torque sensor; the mixing under the first dispersion condition to obtain a premixed slurry includes: Torque signals are continuously acquired in real time using the torque sensor. The apparent viscosity of the slurry is obtained based on the torque signal; When the apparent viscosity of the slurry meets the preset qualified conditions, the pre-dispersion process is deemed qualified, and the premixed slurry is obtained.

[0013] In some embodiments, the preset qualification condition is that the apparent viscosity of the slurry corresponding to three consecutive sampling points is in the range of 800 mPa•s to 1600 mPa•s, and the fluctuation range of the apparent viscosity of the slurry corresponding to the three consecutive sampling points is less than or equal to 8% of the average value of the apparent viscosity of the slurry corresponding to the three consecutive sampling points.

[0014] In some embodiments, in the processing environment corresponding to the second dispersion condition, the epoxy groups carried by the surface modification layer of the first flame-retardant functional unit undergo a ring-opening addition reaction with the primary amine carried by the surface modification layer of the second flame-retardant functional unit to generate a β-hydroxy secondary amine bridging structure.

[0015] Secondly, this application provides a fireproof elevator roller material, which is prepared by the fireproof elevator roller material preparation process described in any one of the first aspects.

[0016] The fireproof elevator roller material provided in this application can improve the problem that the fire-retardant filler settles under gravity during the casting process, resulting in uneven radial distribution of the fire-retardant components in the fireproof elevator roller material, and the inability to simultaneously match the high flame retardant rating and material mechanical properties.

[0017] In some embodiments, the coefficient of variation of the flame-retardant characteristic element phosphorus in the fireproof elevator roller material along the radial cross section of the fireproof elevator roller material is less than or equal to 18%, and the concentration difference of the flame-retardant characteristic element phosphorus between the surface layer and the geometric center region of the fireproof elevator roller material is less than or equal to 10%.

[0018] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is a schematic flowchart illustrating the manufacturing process of fireproof elevator roller material provided in this application embodiment. Detailed Implementation

[0021] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0022] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0023] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0024] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0025] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0026] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a well-known unit of mass in the chemical industry, such as µg, mg, g, or kg.

[0027] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.

[0028] In the process of preparing fireproof elevator roller materials using castable polyurethane elastomers combined with halogen-free flame-retardant fillers, the density of the halogen-free flame-retardant fillers is much greater than that of the liquid polyurethane prepolymer matrix. During the static period after the slurry is dispersed and poured into the mold but before gel solidification, there is no external shear constraint. The halogen-free flame-retardant fillers settle under gravity, resulting in a radial concentration gradient of flame-retardant components in the cured fireproof elevator roller material. To achieve the UL94 V-0 flame retardant rating, a high amount of halogen-free flame-retardant filler needs to be added to the polyurethane prepolymer matrix. However, a high filling ratio of halogen-free flame-retardant filler exacerbates the negative effects of powder settling, ultimately leading to insufficient surface flame-retardant component content and excessive internal accumulation of flame-retardant components in the fireproof elevator roller material. For a long time, the industry has struggled to consistently achieve high flame-retardant ratings for fireproof elevator roller materials while meeting their mechanical performance requirements.

[0029] Based on this, in order to improve the problem in the related technology that the flame-retardant filler settles under gravity during the casting process, resulting in uneven radial distribution of flame-retardant components in the fireproof elevator roller material and the inability to simultaneously match high flame-retardant rating and material mechanical properties, the embodiments of this application provide the following solution.

[0030] Please see Figure 1The first aspect of this application provides a process for preparing fireproof elevator roller materials, applied to a fireproof elevator roller material preparation system. The fireproof elevator roller material preparation system includes a reaction vessel, and the process includes: S100, the first flame-retardant functional unit and the polyurethane prepolymer are added to the reactor and mixed under the first dispersion condition to obtain a premixed slurry; the first flame-retardant functional unit is a submicron flame-retardant filler modified with a silane coupling agent.

[0031] It is understood that the fireproof elevator roller material preparation system is a device used to complete the preparation process of fireproof elevator roller materials, including a wet stirring mill, a reaction vessel, a drive motor, a transmission reducer, a stirring shaft, a dispersion disc, a torque sensor, a temperature control and heat conduction circulation device, a vacuum degassing device, a casting mold, and a post-curing oven.

[0032] The discharge pipe of the wet stirred mill is connected to the solid feeding port at the top of the reactor. The reactor is completely covered by a jacketed structure. Both ends of the jacketed pipe are connected to the medium inlet and outlet of the temperature control and heat conduction circulation device. The drive motor is fixedly installed at the flange position at the top of the reactor. The output shaft of the drive motor is connected downward to the input end of the transmission reducer. The output end of the transmission reducer is coaxially fixedly connected to the upper end of the stirring shaft. The stirring shaft extends vertically downward into the reactor cavity. The lower end of the stirring shaft is fixedly equipped with a dispersion disc. A torque sensor is installed on the coupling between the transmission reducer and the stirring shaft. The discharge pipe at the bottom of the reactor can be switched to connect to the inlet of the vacuum degassing device. The discharge pipe of the vacuum degassing device is connected to the inlet of the casting mold. The entire casting mold can be moved into the cavity of the post-curing oven.

[0033] During operation, after the wet stirred mill completes the grinding and surface modification of the first flame-retardant functional unit, the modified material is transported to the reactor through pipelines. The power output of the drive motor is reduced in speed by the transmission reducer and then transmitted to the stirring shaft. The stirring shaft drives the dispersion disc to rotate inside the reactor to complete the material mixing. The torque sensor continuously collects the torque physical signal generated by the stirring shaft and transmits it outward. The temperature control and heat conduction circulation device delivers heat exchange medium to the reactor jacket to accurately control the temperature of the material inside the reactor. The mixed material is sent to the vacuum degassing device to remove the internal encapsulated air bubbles. The degassed liquid material is transported to the casting mold for shaping. The shaped blank is placed in the post-curing oven for constant temperature post-curing.

[0034] The wet mixing process can be, for example, a vertical circulating wet mixing and grinding mill; the drive motor can be, for example, a variable frequency explosion-proof mixing motor; the transmission reducer can be, for example, a planetary gear reducer; the torque sensor can be, for example, a flange-type strain torque sensor; the temperature control and heat conduction circulation device can be, for example, a heat conduction oil heating and cooling integrated machine; the vacuum degassing device can be, for example, a continuous vacuum mixing and degassing machine; the casting mold can be, for example, a steel roller forming mold; and the post-curing oven can be, for example, a segmented temperature-controlled hot air circulating oven.

[0035] The first flame-retardant functional unit is an inorganic flame-retardant solid material with a median particle size of less than 1 μm, which has undergone surface chemical grafting with a silane coupling agent. Surface modification can be achieved using an organosilicon modifying agent with a ternary epoxy ring functional group. One end of the organosilicon modifying agent can form a bond with the hydroxyl groups on the surface of the inorganic powder, while the other end exposes active chemical groups that can participate in addition reactions. The reaction vessel is an industrial pressure-bearing mixing container with a sealed cavity, temperature control, and stirring capability. The entire mixing process is completed inside the reaction vessel.

[0036] Polyurethane prepolymer is a liquid polyurethane precursor material with isocyanate functional groups at the ends of its molecular chains. It serves as the continuous matrix phase for the fire-resistant elevator roller material after molding. The first dispersion condition is a combination standard that defines the temperature range, stirring speed range, and continuous stirring duration range of the mixing operation in step S100. The premixed slurry is a homogeneous two-phase suspension formed after the first flame-retardant functional unit and the polyurethane prepolymer are mixed inside the reactor under the first dispersion condition.

[0037] For example, first, all feeding and venting channels of the reactor are closed to form a sealed cavity. Polyurethane prepolymer is then fed into the reactor through a liquid feeding pipeline, followed by the addition of a dried first flame-retardant functional unit through a solid feeding pipeline. The drive motor is started to rotate the dispersion disc continuously, while a temperature-controlled heat transfer circulation device is simultaneously activated to introduce heat exchange medium into the reactor jacket. This maintains the material inside the reactor within the temperature range corresponding to the first dispersion condition. The dispersion disc continues to rotate for a set time, after which stirring is stopped, completing the preparation of the premixed slurry. During operation, a phased solid feeding method can be used to add the first flame-retardant functional unit into the reactor multiple times, mitigating the problem of a sudden and significant increase in the viscosity of the slurry inside the reactor caused by a large-scale one-time addition of the first flame-retardant functional unit.

[0038] With this configuration, the first flame-retardant functional unit with submicron dimensions, after being uniformly dispersed within the polyurethane prepolymer, can form a reversible spatial network structure within the premixed slurry system. This reversible spatial network structure can provide support for the subsequently added second flame-retardant functional unit, reducing its settling velocity during the static process. This helps alleviate the uneven distribution of flame-retardant components along the radial direction of the molded fireproof elevator roller material. The compatibility between the first flame-retardant functional unit modified with the silane coupling agent and the polyurethane prepolymer interface is improved, which can balance the flame-retardant rating and mechanical properties of the finished fireproof elevator roller material.

[0039] S200, a second flame-retardant functional unit is added to the premixed slurry and mixed under the second dispersion conditions. The first active group carried by the surface modification layer of the first flame-retardant functional unit reacts chemically with the second active group carried by the surface modification layer of the second flame-retardant functional unit to form a covalent bridging structure between the first flame-retardant functional unit and the second flame-retardant functional unit, thereby obtaining a modified composite slurry. The second flame-retardant functional unit is a micron-sized flame-retardant filler modified with a silane coupling agent.

[0040] It can be understood that the second flame-retardant functional unit is an inorganic flame-retardant solid material with an overall median particle size in the range of 1μm to 10μm, which has undergone surface chemical grafting with a silane coupling agent. Surface modification can be achieved using an organosilicon modifying agent with primary amino functional groups. One end of the organosilicon modifying agent can form a bond with the hydroxyl groups on the surface of the inorganic powder, while the other end exposes an active chemical group that can undergo addition reactions with epoxy groups. The surface modification layer is a monomolecular thin layer formed by silane coupling agent molecules stably adhering to the outer surface of the flame-retardant filler through chemical bonds. The first active group is a silane-modified chemical group on the surface of the first flame-retardant functional unit that can undergo addition reactions with other functional groups; for example, a three-membered epoxy ring structure can be selected. The second active group is a silane-modified chemical group on the surface of the second flame-retardant functional unit that can undergo addition reactions with epoxy groups; for example, a primary amino structure can be selected.

[0041] Chemical reactions are intermolecular addition transformation processes between two different types of active functional groups. The specific reaction type corresponding to this application is the ring-opening addition between a three-membered epoxy ring functional group and a primary amine functional group. The covalent bridging structure is a molecular-level connection structure established between the two types of flame-retardant functional units by forming covalent chemical bonds through chemical reactions between the active functional groups of silane coupling agent molecules grafted onto the surface of the first flame-retardant functional unit and silane coupling agent molecules grafted onto the surface of the second flame-retardant functional unit. The second dispersion condition is a combination standard that limits the temperature range of mixing in step S200, the stirring speed range of the dispersion disc, and the continuous stirring time range of process parameters. The modified composite slurry is a composite solid-liquid suspension material obtained after the first flame-retardant functional unit, the second flame-retardant functional unit, and the polyurethane prepolymer are mixed under the second dispersion condition inside the reactor and the corresponding chemical reaction is completed.

[0042] For example, the reactor is kept sealed with no air circulation. The dried second flame-retardant functional unit is fed into the premixed slurry inside the reactor through the solid feeding pipeline. The output power of the drive motor is increased to improve the speed of the dispersion disc. The temperature of the heat exchange medium of the temperature control heat conduction circulation device is adjusted simultaneously to maintain the material inside the reactor within the temperature range corresponding to the second dispersion condition. Nitrogen gas is continuously introduced into the reactor throughout the stirring process to create an inert and sealed environment, reducing the probability of the silane coupling agent self-condensation side reaction caused by trace moisture inside the slurry. The dispersion disc is continuously stirred for the set time. The epoxy groups on the surface of the first flame-retardant functional unit and the primary amino functional groups on the surface of the second flame-retardant functional unit come into full contact to complete the intermolecular ring-opening addition conversion. A covalent bridging structure is generated between the two types of flame-retardant functional units to obtain a modified composite slurry.

[0043] This configuration creates a stable covalent bridge structure between the first and second flame-retardant functional units. The two types of solid flame-retardant functional units form a mutually restraining micro-crosslinking system, which can reduce the settling tendency of the first and second flame-retardant functional units during the casting and standing stage. This helps to reduce the difference in flame-retardant element concentration between the surface and geometric center of the fireproof elevator roller material. The covalent bond structure can improve the interfacial bonding strength between the two types of flame-retardant solid materials and the polyurethane matrix, and can simultaneously maintain the high flame-retardant rating and excellent mechanical properties of the finished material.

[0044] S300 involves adding a curing agent to a modified composite slurry, followed by degassing, casting, and post-curing to obtain a fireproof elevator roller material.

[0045] It is understood that the curing agent is an organic diamine chemical reagent that can cross-link and transform the isocyanate group at the end of the polyurethane prepolymer molecule, converting the liquid slurry into a solid elastomer. For example, 3,3'-dichloro-4,4'-diaminodiphenylmethane can be used. Degassing is a process of removing micro-bubbles trapped inside the modified composite slurry under negative pressure; the entire process is completed inside a vacuum degassing device. Casting is the process of conveying the bubble-free liquid modified composite slurry into the cavity of a casting mold, initially shaping it into the form of a fireproof elevator roller material blank. Post-curing is a process of placing the demolded fireproof elevator roller material blank into a post-curing oven, where it is heated in stages to maintain a constant temperature, completing the remaining cross-linking transformation and releasing the internal stress of the molding. The fireproof elevator roller material is a flame-retardant polyurethane solid elastomer material produced using S100 to S300 processes, suitable for the outer layer coating of fireproof elevator rollers.

[0046] For example, while maintaining a low-speed stirring state in the reactor, a preheated curing agent is added to the modified composite slurry inside the reactor. Low-speed stirring ensures uniform mixing of the curing agent and the modified composite slurry. After mixing, the slurry is transported to a vacuum degassing device. Gradient negative pressure is used to gradually reduce the chamber pressure (e.g., -0.03 MPa for 3 minutes in the first stage, -0.06 MPa for 4 minutes in the second stage, and -0.09 MPa for 5 minutes in the third stage), gently releasing the tiny air bubbles inside the slurry. The degassed liquid slurry is then transported to a preheated casting mold cavity for initial shaping. After demolding, the shaped blank is transferred as a whole to a post-curing oven, where it is heated in stages according to a preset heating rate and kept at a constant temperature (e.g., 80℃ for 1 hour, 110℃ for 2 hours, and 140℃ for 1.5 hours), ultimately yielding the fireproof elevator roller material. Gradient negative pressure degassing can reduce the occurrence of material splashing and residual large pores caused by rapid release of bubbles under high negative pressure in a single operation.

[0047] This setup, with its gradient negative pressure degassing and segmented heating followed by curing, can reduce internal pores and internal stress defects in the fireproof elevator roller material, improve the uniformity of the overall fireproof elevator roller material structure, and mitigate the flame-retardant delamination problem caused by local mechanical weaknesses. It also helps to alleviate the radial performance differences in the fireproof elevator roller material caused by the settlement of the first and second flame-retardant functional units.

[0048] As can be seen from the above, the fireproof elevator roller material preparation process provided in this application embodiment, through stepwise dispersion, in-situ covalent bridging of flame-retardant functional units, and gradient molding continuous process operation, can reduce the negative impact of gravity settling of the first and second flame-retardant functional units from two levels: the cross-linking structure of the micro-flame-retardant functional units and the macro-molding control. It also reduces the difference in the distribution of flame-retardant elements along the radial direction of the fireproof elevator roller material. Without adding additional thickening agents, it is beneficial to simultaneously achieve a high flame-retardant rating and balanced mechanical properties of the material.

[0049] In some embodiments, the curing agent is 3,3'-dichloro-4,4'-diaminodiphenylmethane; the amount of curing agent used is based on the isocyanate content of the polyurethane prepolymer. The molar ratio was determined to be between 0.85 and 0.95.

[0050] It is understandable that 3,3'-dichloro-4,4'-diaminodiphenylmethane is an aromatic diamine curing raw material with two sets of primary amine functional groups in its molecular structure. These primary amine functional groups can undergo cross-linking transformation with the isocyanate group of the polyurethane prepolymer. The isocyanate group is the -NCO active functional group present at the end of the polyurethane prepolymer molecular chain, serving as the reaction site for curing and cross-linking transformation. The NH2 / NCO molar ratio is the ratio of the total amount of primary amine substances within the curing agent to the total amount of isocyanate substances within the polyurethane prepolymer. This ratio is used to precisely control the degree of completion of the polyurethane cross-linking transformation. When the molar ratio of NH2 / NCO is below 0.85, there is an excess of isocyanate in the system, resulting in insufficient crosslinking density and decreased mechanical strength after curing. When the molar ratio is above 0.95, there is an excess of primary amines in the system, and unreacted free primary amines remain inside the material. These amines are prone to precipitate under high-temperature conditions, reducing flame retardant stability. A molar ratio of NH2 / NCO in the range of 0.85 to 0.95 can balance the integrity of crosslinking and the thermal stability of the finished product.

[0051] For example, the amount of curing agent can be determined by first measuring the mass fraction of isocyanate in the polyurethane prepolymer using standard titration, and then using 42 g / mol as the molar mass of isocyanate to calculate the amount of isocyanate substance per unit mass of polyurethane prepolymer. This is then combined with a pre-set... The molar ratio is used to deduce the total amount of primary amino groups required in the system. A single molecule of 3,3'-dichloro-4,4'-diaminodiphenylmethane contains two groups of primary amino groups. The molar mass of 3,3'-dichloro-4,4'-diaminodiphenylmethane is 267 g / mol. Combining this with the total amount of primary amino groups, the corresponding weight of the curing agent can be calculated. Before adding the curing agent, heat it to 60°C to 80°C to reduce its viscosity, ensuring thorough mixing of the curing agent and the modified composite slurry.

[0052] This setup, by accurately calculating the amount of curing agent added according to the fixed molar ratio of primary amines and isocyanates, ensures that the polyurethane crosslinking conversion is complete and the crosslinking density is stable. This reduces the dispersion of mechanical properties of different batches of finished materials, improves the overall mechanical uniformity of the material, and weakens the risk of flame retardant failure caused by local filler sedimentation and insufficient crosslinking.

[0053] In some embodiments, the fireproof elevator roller material preparation system includes a wet stirred mill; the preparation method of the first flame-retardant functional unit includes: S400 involves adding melamine polyphosphate and zirconia grinding beads with a diameter of 0.3 mm to 0.5 mm into a wet stirred mill at a mass ratio of 1:8 to 1:12, using deionized water as the grinding medium, and performing a circulating grinding process at a speed of 2000 rpm to 3000 rpm for 8 to 16 hours to obtain a grinding slurry. The median particle size D50 of the melamine polyphosphate in the grinding slurry after grinding is less than or equal to 500 nm, and the particle size D90 is less than or equal to 800 nm.

[0054] It is understandable that wet stirred mills are circulating grinding equipment that relies on the high-speed impact and shearing of hard grinding beads to refine materials; for example, a vertical circulating wet stirred mill. Melamine polyphosphate is a phosphorus-nitrogen composite inorganic flame-retardant solid material and a basic raw material for preparing the first flame-retardant functional unit. Zirconia grinding beads are high-hardness spherical zirconia media particles used to break up agglomerated materials through mechanical force. When the diameter of zirconia grinding beads is less than 0.3 mm, the impact kinetic energy of a single zirconia grinding bead is insufficient to completely break up hard agglomerates. When the diameter is greater than 0.5 mm, the number of zirconia grinding beads filling the cavity decreases, the shearing impact frequency decreases, and the refining efficiency deteriorates. A diameter of 0.3 mm to 0.5 mm can balance impact kinetic energy and filling density.

[0055] When the mass ratio of melamine polyphosphate to zirconia grinding beads is less than 1:12, there is an excess of zirconia grinding beads, leading to a significant increase in grinding energy consumption. When the ratio is greater than 1:8, the concentration of melamine polyphosphate in the grinding chamber is too high, preventing the zirconia grinding beads from fully contacting all particles, resulting in incomplete agglomeration and breakup. A mass ratio between 1:8 and 1:12 balances grinding efficiency and equipment energy consumption. Deionized water, a pure liquid material free of metal and impurity ions, serves as the grinding medium for transmitting the shear force of the zirconia grinding beads and dispersing the melamine polyphosphate. When the rotation speed is below 2000 rpm, the shear force is insufficient, and the melamine polyphosphate cannot be refined to the submicron range. When the rotation speed is above 3000 rpm, the frictional heat increases sharply, causing the melamine polyphosphate to easily agglomerate at high temperatures and accelerating the wear of seals. A rotation speed range of 2000 to 3000 rpm balances refining effect and equipment lifespan.

[0056] Circulating grinding for less than 8 hours cannot completely break up large agglomerates, while grinding for more than 16 hours increases energy consumption exponentially without significantly optimizing the size of melamine polyphosphate. Circulating grinding for 8 to 16 hours can stably produce melamine polyphosphate with the required particle size. Circulating grinding involves the continuous reciprocating flow of melamine polyphosphate, deionized water, and zirconia grinding beads between the grinding chamber of a wet stirred mill and external pipelines, which improves the overall particle size uniformity of melamine polyphosphate. The grinding slurry is a suspension mixture formed by mixing melamine polyphosphate, deionized water, and zirconia grinding beads. The median particle size D50 is a statistical parameter for the volumetric particle size of melamine polyphosphate, representing the particle diameter corresponding to a cumulative volume fraction of 50%, used to characterize the overall average size of melamine polyphosphate. Particle size D90 is a statistical parameter for the volumetric particle size of melamine polyphosphate, representing the particle diameter when the cumulative volume of melamine polyphosphate reaches 90%. It is used to control the maximum size of coarse particles within the system. Limiting the two particle size values ​​of melamine polyphosphate can reduce the problem of rapid sedimentation caused by large particles.

[0057] With this setup, long-term cyclic wet grinding combined with appropriately sized zirconia grinding beads can refine melamine polyphosphate to the submicron range. The driving force of single particle gravity settling decreases, which can alleviate the settling speed of the first flame-retardant functional unit during the subsequent slurry settling stage. The dual control of median particle size D50 and particle size D90 can reduce the residue of coarse agglomerates, improve the dispersion uniformity of the first flame-retardant functional unit in the polyurethane prepolymer, and reduce the radial flame-retardant component concentration difference of the fireproof elevator roller material after molding.

[0058] S500 involves adding γ-glycidyl etheroxypropyltrimethoxysilane to a grinding slurry at 1% to 3% of the mass of melamine polyphosphate, stirring and reacting at 60°C to 80°C for 2 to 4 hours, and then spray drying the material after the reaction to obtain the first flame-retardant functional unit.

[0059] It is understandable that γ-glycidoxypropyltrimethoxysilane is an organosilicon modifying agent with a siloxane group at one end and a three-membered epoxy ring functional group at the other end. The siloxane group can bond with the hydroxyl groups on the surface of melamine polyphosphate, while the exposed epoxy group serves as a site for subsequent addition reactions. When the amount of γ-glycidoxypropyltrimethoxysilane added is less than 1% of the mass of melamine polyphosphate, the surface coating of melamine polyphosphate is incomplete, and the number of active sites is insufficient to form sufficient interparticle covalent bonds. When the amount is more than 3% of the mass of melamine polyphosphate, the excess γ-glycidoxypropyltrimethoxysilane undergoes self-polymerization to form oligomers, reducing the mechanical properties of the finished product. The range of 1% to 3% can achieve complete monolayer coating of melamine polyphosphate.

[0060] When the stirring reaction temperature is below 60℃, the hydrolysis and grafting rate of γ-glycidoxypropyltrimethoxysilane is too slow, and surface modification cannot be completed in a short time. When the temperature is above 80℃, γ-glycidoxypropyltrimethoxysilane rapidly self-condenses, consuming active molecules and generating non-reactive oligomeric siloxanes, reducing the number of epoxy sites that can participate in ring-opening addition. The grafting reaction rate and the utilization efficiency of γ-glycidoxypropyltrimethoxysilane are balanced in the 60℃ to 80℃ range. When the stirring reaction time is less than 2 hours, the grafting conversion of γ-glycidoxypropyltrimethoxysilane is incomplete, and the thickness of the melamine polyphosphate surface modification layer is uneven. When the time is greater than 4 hours, the self-polymerization ratio of free γ-glycidoxypropyltrimethoxysilane in the system increases significantly, and uniform monomolecular coating can be completed in the 2- to 4-hour range.

[0061] The stirring reaction process involves the hydrolytic grafting of γ-glycidyl etheroxypropyltrimethoxysilane onto the surface hydroxyl groups of melamine polyphosphate under a constant-temperature stirring environment. The spray drying process involves atomizing the reacted material and passing it through a low-temperature hot air stream to remove liquid deionized water, resulting in a dry, solid first flame-retardant functional unit. For example, the spray drying parameters are: inlet air temperature 180℃ to 220℃, outlet air temperature 80℃ to 100℃, feed rate 50mL / min to 200mL / min, and atomizing disc rotation speed 15000rpm to 25000rpm. The material collected after spray drying is then subjected to a second drying process under vacuum at 80℃ for 2 hours to remove residual adsorbed water, yielding the first flame-retardant functional unit.

[0062] This setup, adapting to the addition amount, temperature, and duration of the γ-glycidyl etheroxypropyltrimethoxysilane grafting reaction, allows for the uniform coating of a monomolecular γ-glycidyl etheroxypropyltrimethoxysilane layer on the surface of melamine polyphosphate. This stably introduces epoxy active sites, providing sufficient reaction sites for the ring-opening addition and covalent bridging structure construction between the first and second flame-retardant functional units in step S200. After airflow depolymerization, the first flame-retardant functional unit exhibits no hard agglomeration, improving its dispersion effect within the polyurethane prepolymer. This further alleviates the problem of uneven component distribution in the fireproof elevator roller material caused by the settling of the first and second flame-retardant functional units during the casting stage.

[0063] By employing the aforementioned S400 to S500, submicron-level melamine polyphosphate refinement and γ-glycidyl etheroxypropyltrimethoxysilane surface-active functional group modification can be completed simultaneously. Refining melamine polyphosphate reduces the driving force for single-particle sedimentation, while γ-glycidyl etheroxypropyltrimethoxysilane modification provides covalent bridging reaction sites. These two effects work synergistically to alleviate the stratification phenomenon of flame-retardant fillers during the casting and molding stage, which is beneficial to balancing the flame-retardant uniformity and mechanical properties of the finished fireproof elevator roller material.

[0064] In some embodiments, the first flame-retardant functional unit is a submicron-sized melamine polyphosphate modified with γ-glycidoxypropyltrimethoxysilane, the median particle size D50 of the first flame-retardant functional unit is 200 nm to 500 nm, and the modification mass of γ-glycidoxypropyltrimethoxysilane is 1% to 3% of the mass of the submicron-sized melamine polyphosphate; the second flame-retardant functional unit is a micron-sized aluminum diethylphosphonate modified with γ-aminopropyltriethoxysilane, the median particle size D50 of the second flame-retardant functional unit is 3 μm to 8 μm, and the modification mass of γ-aminopropyltriethoxysilane is 0.5% to 1.5% of the mass of the micron-sized aluminum diethylphosphonate.

[0065] It is understandable that micron-sized diethylphosphinate aluminum is a micron-scale phosphorus-based inorganic flame-retardant solid material and a basic raw material for preparing the second flame-retardant functional unit. When the modification mass of γ-aminopropyltriethoxysilane is less than 0.5% of the mass of micron-sized diethylphosphinate aluminum, the number of γ-aminopropyltriethoxysilane grafted onto the surface of micron-sized diethylphosphinate aluminum is insufficient, resulting in fewer exposed primary amino sites. When it is higher than 1.5%, the amount of free γ-aminopropyltriethoxysilane self-polymers increases, reducing the mechanical properties of the finished product. A range of 0.5% to 1.5% can achieve complete monomolecular coating of micron-sized diethylphosphinate aluminum.

[0066] The selection logic for the median particle size D50 of 200nm to 500nm for the first flame-retardant functional unit and 3μm to 8μm for the second flame-retardant functional unit is as follows: Submicron-sized melamine polyphosphate and micron-sized aluminum diethylphosphonate form a dual-scale compound system. This combination improves material packing density, reduces the free flow space within the slurry, and decreases settling channels. When the particle size ranges of the two types of materials overlap, hierarchical packing cannot be formed, and a stable anti-settling network structure cannot be constructed. Submicron-sized materials fill the gaps between micron-sized materials, significantly reducing the free flow channels within the slurry and decreasing the space for free settling. Modification quality is the percentage of the corresponding silicone modifier input mass to the total mass of the corresponding flame-retardant solid material raw material, used to quantitatively control the coating thickness of the silicone modifier on the surface of the flame-retardant solid material.

[0067] This configuration, combining submicron-scale melamine polyphosphate modified with γ-glycidoxypropyltrimethoxysilane with a micron-scale aluminum diethylphosphonate modified with γ-aminopropyltriethoxysilane, creates a dual-scale flame-retardant system. This system simultaneously forms a submicron-scale melamine polyphosphate thixotropic anti-settling network and a covalently cross-linked framework between the first and second flame-retardant functional units within the slurry. The dual structure synergistically reduces the gravitational settling rate of the submicron-scale melamine polyphosphate and the micron-scale aluminum diethylphosphonate. After molding, the uniformity of the radial distribution of flame-retardant elements in the fireproof elevator roller material is improved, simultaneously meeting both high flame-retardant standards and balanced mechanical performance requirements.

[0068] In some embodiments, the preparation method of the second flame-retardant functional unit includes: placing micron-sized aluminum diethylphosphonate into a high-speed mixer, preheating it to 60°C to 70°C, adding γ-aminopropyltriethoxysilane at 0.5% to 1.5% of the mass of the micron-sized aluminum diethylphosphonate in a spray manner into the high-speed mixer, continuously stirring and reacting at a speed of 1200 rpm to 1500 rpm for 15 min to 30 min, and drying the material after discharge to obtain the second flame-retardant functional unit.

[0069] It is understandable that high-speed mixing dry modification is a conventional process for silane modification of micron-sized inorganic filler surfaces. This process is simple to operate, requires no subsequent large-scale drying and dehydration steps, and is suitable for the batch surface modification treatment of micron-sized diethylphosphinate aluminum. γ-aminopropyltriethoxysilane forms stable silicon-oxygen bonds with the hydroxyl groups on the surface of micron-sized diethylphosphinate aluminum through hydrolysis, while the primary amine at the other end is exposed, serving as the active site for subsequent ring-opening addition reactions.

[0070] In some embodiments, the reactor includes a dispersion plate; the first dispersion conditions are a processing temperature of 50°C to 80°C, a stirring speed of 500 rpm to 800 rpm, and a mixing time of 15 min to 30 min; the second dispersion conditions are a processing temperature of 80°C to 100°C, a stirring speed of 800 rpm to 1200 rpm, and a mixing time of 20 min to 40 min.

[0071] It can be understood that the dispersing disc is a multi-toothed disc-shaped stirring actuator fixed to the lower end of the stirring shaft. The stirring shaft drives the dispersing disc to rotate synchronously, and the shearing force generated by the teeth of the dispersing disc breaks up material agglomerates, achieving uniform mixing of solid and liquid materials. The processing temperature is the uniform temperature of all materials inside the reactor after being regulated by the temperature control and heat conduction circulation device. The stirring speed is the number of complete rotations of the dispersing disc per minute driven by the drive motor. The mixing time is the continuous operating time during which the dispersing disc rotates continuously and the material inside the reactor maintains a stable corresponding temperature.

[0072] When the processing temperature of the first dispersion condition is below 50℃, the viscosity of the polyurethane prepolymer is too high, making it difficult to uniformly wet and disperse the submicron-sized melamine polyphosphate. Above 80℃, the three-membered epoxy ring functional groups carried by γ-glycidyl etheroxypropyltrimethoxysilane decompose prematurely and slowly, losing active sites. The 50℃ to 80℃ range is suitable for the wetting and dispersion requirements of materials in the premixing stage. When the stirring speed of the dispersion disc is below 500 rpm, the shear force at the toothed end of the dispersion disc is insufficient, and the agglomeration of submicron-sized melamine polyphosphate cannot be completely dispersed. Above 800 rpm, the strong shear force destroys the reversible thixotropic network constructed by submicron-sized melamine polyphosphate in the premixing stage, causing the slurry to lose its anti-settling ability. The 500 rpm to 800 rpm range balances material dispersion and the preservation of the reversible thixotropic network structure. When the mixing time is less than 15 min, the submicron-sized melamine polyphosphate is not completely dispersed, and the network structure cannot be fully formed. When the mixing time is greater than 30 min, it increases production energy consumption without significantly improving the network structure.

[0073] The second dispersion condition, with a processing temperature of 80℃ to 100℃, is suitable for the ring-opening addition reaction between the ternary epoxy ring functional group and the primary amine functional group. Below 80℃, the reaction rate is extremely low, and above 100℃, the ternary epoxy ring functional group undergoes thermal decomposition. A dispersion disc stirring speed of 800 rpm to 1200 rpm is suitable for breaking up the high-hardness agglomerates of micron-sized diethylphosphinate. Higher tooth-end shear force can completely disperse the micron-sized diethylphosphinate while providing sufficient collision kinetics. When the mixing time is less than 20 minutes, the addition reaction between the ternary epoxy ring functional group and the primary amine functional group is incomplete, and the number of covalent bridging structures between the submicron-sized melamine polyphosphate and the micron-sized diethylphosphinate is insufficient. When the mixing time is greater than 40 minutes, energy consumption increases without a significant improvement in the degree of reaction. The 20-40 minute range balances reaction integrity and production efficiency.

[0074] This setup allows for stable dispersion of submicron-sized melamine polyphosphates at low temperature and low speed, constructing a reversible thixotropic anti-settling network within the slurry. The secondary dispersion at high temperature and high speed disperses micron-sized aluminum diethylphosphinate while providing a suitable environment for the ring-opening addition reaction of ternary epoxy ring functional groups and primary amine functional groups. This two-stage differentiated dispersion reduces the agglomeration and particle stratification of submicron-sized melamine polyphosphates and micron-sized aluminum diethylphosphinates, thus minimizing the difference in flame-retardant element concentration between the surface and geometric center areas of the fireproof elevator roller material.

[0075] In some embodiments, the reactor is provided with a stirring shaft, and the stirring shaft is equipped with a torque sensor; S100, mixing is carried out under the first dispersion condition to obtain a premixed slurry, comprising: The S110 continuously acquires torque signals in real time through a torque sensor.

[0076] The stirring shaft is a vertically oriented transmission rod that runs through the reactor cavity, connecting to a drive reducer at the top and a dispersion disc at the bottom, used to transmit the rotational power of the drive motor. The torque sensor is a sensing element installed at the coupling between the drive reducer and the stirring shaft. For example, a flange-type strain torque sensor can be used. The torque sensor captures the physical quantity of torque generated by the material resistance during the rotation of the stirring shaft and converts it into a standardized continuous electrical signal output. The torque signal is an analog electrical signal obtained by the torque sensor from the torque of the stirring shaft, used for subsequent calculation of the apparent viscosity of the slurry.

[0077] For example, the torque sensor continuously captures the real-time torque physical quantity of the stirring shaft at fixed time intervals, and simultaneously converts the torque physical quantity into a 4-20mA standardized analog electrical signal and transmits it to the PLC controller in real time to complete continuous recording.

[0078] S120, the apparent viscosity of the slurry is obtained based on the torque signal.

[0079] It is understandable that the apparent viscosity of the slurry is a fluid viscosity resistance parameter of the premixed slurry. The value of the apparent viscosity of the slurry is directly related to the dispersion uniformity of the first flame-retardant functional unit and the integrity of the thixotropic network inside the reactor.

[0080] For example, multiple sets of known standard viscosity liquid media (such as standard dimethyl silicone oil) are first selected. Under the same reaction vessel, the same dispersion plate, the same stirring speed, and the same 60°C calibration temperature, the stable torque corresponding to each set of standard viscosity liquid media is collected. At standard viscosity The vertical axis corresponds to the stable torque. Using the horizontal axis as the x-axis, a linear regression fit yields the formula. =K· Where K is the linear conversion coefficient, and in the actual premixing stage, the torque collected in real time is directly used. Substitute into the formula =K· Obtain the real-time apparent viscosity of the slurry Then, substitute the Arrhenius temperature compensation formula to correct the temperature deviation: , The activation energy of the polyurethane slurry is 38 kJ / mol. =333K (60℃), correcting for viscosity calculation errors caused by temperature fluctuations in the material inside the reactor. This refers to the apparent viscosity of the slurry.

[0081] S130: When the apparent viscosity of the slurry meets the preset qualified conditions, the pre-dispersion process is deemed qualified, and a premixed slurry is obtained.

[0082] It is understandable that the preset qualification conditions are the constraint judgment rules for the output standard of the premixing process in control step S100. For example, they may consist of two parts: the range constraint of the apparent viscosity of the slurry and the relative fluctuation range constraint of the apparent viscosity of the slurry. The qualification of the pre-dispersion process means that the dispersion of the first flame retardant functional unit and the formation of the thixotropic network meet the process standards, and can proceed to the subsequent secondary dispersion process in S200.

[0083] By adopting the above-mentioned S110 to S130, the formation state of the anti-settling network inside the premixed slurry can be accurately controlled, reducing network damage and batch performance dispersion caused by manual sampling, and stabilizing the gravity stratification phenomenon of the first flame-retardant functional unit and the second flame-retardant functional unit during the casting stage.

[0084] In some embodiments, the preset qualification condition is that the apparent viscosity of the slurry corresponding to three consecutive sampling points is in the range of 800 mPa•s to 1600 mPa•s, and the fluctuation range of the apparent viscosity of the slurry corresponding to the three consecutive sampling points is less than or equal to 8% of the average value of the apparent viscosity of the slurry corresponding to the three consecutive sampling points.

[0085] It can be understood that the sampling point is a fixed time node corresponding to a single torque acquisition by the torque sensor and the conversion of the apparent viscosity of the slurry. When the fluctuation range of the apparent viscosity of the slurry corresponding to three consecutive sampling points is greater than 8% of the average apparent viscosity of the slurry corresponding to the three consecutive sampling points, it indicates that the first flame-retardant functional unit inside the reactor is unevenly dispersed, and the thixotropic network constructed by the first flame-retardant functional unit is partially missing, which will reduce the ability of the slurry to inhibit particle sedimentation during the settling stage. The fluctuation range is the absolute value of the difference between the apparent viscosity of the slurry at a single sampling point and the average apparent viscosity of the slurry corresponding to the three consecutive sampling points, divided by the average value to obtain the relative deviation.

[0086] With this setting, the range constraint of the apparent viscosity of the slurry, combined with the fluctuation range constraint of the average value reference of the apparent viscosity of the slurry, can dually control the viscosity of the premixed slurry and the dispersion uniformity and stability of the first flame retardant functional unit. The static anti-settling performance of the premixed slurry remains stable from batch to batch, and the radial flame retardant element distribution difference of the fireproof elevator roller material after molding is reduced.

[0087] In some embodiments, in the processing environment corresponding to the second dispersion condition, the epoxy groups carried by the surface modification layer of the first flame-retardant functional unit undergo a ring-opening addition reaction with the primary amine carried by the surface modification layer of the second flame-retardant functional unit to generate a β-hydroxy secondary amine bridging structure.

[0088] It can be understood that the epoxy group is the three-membered cyclic ether functional group at the end of the organosilicon modifying agent molecule used to modify the first flame-retardant functional unit. The primary amine is the primary amine functional group at the end of the organosilicon modifying agent molecule used to modify the second flame-retardant functional unit. The ring-opening addition reaction is an intermolecular transformation reaction between the functional group with the cyclic epoxy structure and the primary amine functional group. After the cyclic epoxy chemical bond is opened, it forms a stable carbon-nitrogen covalent bond with the primary amine. The β-hydroxy secondary amine bridging structure is a molecular linking chain generated after the three-membered epoxy ring functional group and the primary amine complete the ring-opening addition transformation. This molecular linking chain can connect the first and second flame-retardant functional units to each other through stable covalent chemical bonds.

[0089] This configuration creates a stable covalent bridge structure between the first and second flame-retardant functional units. The two types of solid flame-retardant functional units form a mutually restraining micro-crosslinking system, which can reduce the settling tendency of the first and second flame-retardant functional units during the casting and standing stage. This helps to reduce the difference in flame-retardant element concentration between the surface and geometric center of the fireproof elevator roller material. The covalent bond structure can improve the interfacial bonding strength between the two types of flame-retardant solid materials and the polyurethane matrix, and can simultaneously maintain the high flame-retardant rating and excellent mechanical properties of the finished material.

[0090] The second aspect of this application provides a fireproof elevator roller material, which is prepared by the fireproof elevator roller material preparation process of any one of the first aspects.

[0091] It is understandable that the fireproof elevator roller material is a solid flame-retardant polyurethane elastic preform obtained after fully implementing the complete set of fireproof elevator roller material preparation processes from S100 to S300.

[0092] As can be seen from the above, the fireproof elevator roller material provided in this application embodiment can improve the problem that the fire-retardant filler settles under gravity during the casting process, resulting in uneven radial distribution of the fire-retardant components in the fireproof elevator roller material, and the inability to simultaneously match the high flame retardant rating and material mechanical properties.

[0093] In some embodiments, the coefficient of variation of the surface distribution of the flame-retardant characteristic element phosphorus in the fireproof elevator roller material along the radial section of the fireproof elevator roller material is less than or equal to 18%, and the concentration difference of the flame-retardant characteristic element phosphorus between the surface layer and the geometric center region of the fireproof elevator roller material is less than or equal to 10%.

[0094] It is understandable that phosphorus, a characteristic flame-retardant element, is a common characteristic chemical element found in both the first and second flame-retardant functional units of phosphorus-based solid flame-retardant materials. It is used to quantitatively determine the uniformity of the distribution of flame-retardant components within fire-resistant elevator roller materials. The radial section is a flat test section obtained by completely cutting along the diameter and thickness direction of the entire fire-resistant elevator roller material. The surface distribution variation coefficient is calculated by dividing the standard deviation of phosphorus content at all points on the flat test section by the arithmetic mean of phosphorus content at all points on the flat test section after scanning the phosphorus content using an electron probe. The 18% threshold is based on the fact that in a non-covalently bridged physical blend system with the same total filler addition, this value is typically higher than 25%, while a value lower than 18% indicates that there is no significant local enrichment or deficiency of phosphorus element within the flat test section.

[0095] The surface layer is the testing area extending 0.5mm inward from the outermost surface of the radial section of the fireproof elevator roller material. The geometric center area is the internal testing area within a 2mm diameter circle centered on the geometric center point of the radial section of the fireproof elevator roller material. The concentration difference is calculated by collecting the average phosphorus content of the surface layer and the average phosphorus content of the geometric center of the flat testing section, and then dividing the absolute value of the difference between the average phosphorus content of the surface layer and the average phosphorus content of the geometric center by the arithmetic mean of the total phosphorus content of the flat testing section to obtain a percentage value. The upper limit of 10% is determined by the fact that a value higher than 10% indicates a relative lack of flame-retardant material on the surface and a relative enrichment of flame-retardant material inside, resulting in significant fluctuations in the local flame-retardant performance of the finished product.

[0096] This setup allows for a clear demonstration of the actual effect of this preparation process in mitigating the settling of flame-retardant fillers. With both indicators controlled within their respective ranges, the flame-retardant performance of the entire fireproof elevator roller material remains stable at any location, reducing the occurrence of defects such as surface flame-retardant failure and decreased mechanical properties due to internal filler enrichment.

[0097] The following description is based on specific embodiments.

[0098] Example 1: Raw material formulation: 100 parts of polyester-type polyurethane prepolymer (NCO mass fraction 4.2%); 12.0 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane ( (Molar ratio of 0.90); 12 parts of the first flame-retardant functional unit; 16 parts of the second flame-retardant functional unit.

[0099] The first flame-retardant functional unit is a submicron-sized melamine polyphosphate modified with γ-glycidoxypropyltrimethoxysilane, with a median particle size D50 of 350 nm and a modification mass of γ-glycidoxypropyltrimethoxysilane of 2% of the mass of melamine polyphosphate; the second flame-retardant functional unit is a micron-sized aluminum diethylphosphonate modified with γ-aminopropyltriethoxysilane, with a median particle size D50 of 5 μm and a modification mass of γ-aminopropyltriethoxysilane of 1.0% of the mass of aluminum diethylphosphonate.

[0100] Preparation process: 1. Raw material pretreatment: The first flame retardant functional unit is vacuum dried at 80℃ for 2 hours; the second flame retardant functional unit is blown dry at 60℃ for 4 hours; the polyester polyurethane prepolymer is preheated at 60℃.

[0101] 2. Pre-dispersion stage: The first flame-retardant functional unit and the polyester polyurethane prepolymer are added to the reactor and mixed for 20 minutes at 60℃ and 600 rpm to obtain a premixed slurry. During the mixing process, the torque signal is collected in real time by a torque sensor and the apparent viscosity of the slurry is calculated. When the apparent viscosity of the slurry at three consecutive sampling points is in the range of 800-1600 mPa•s and the fluctuation range is ≤8%, the pre-dispersion is deemed qualified.

[0102] 3. Secondary dispersion and bridging stage: Add the second flame retardant functional unit to the premixed slurry, heat to 90℃, increase the speed of the dispersion disk to 1050rpm, and mix for 30min to obtain the modified composite slurry.

[0103] 4. Degassing and mixing with curing agent: Cool to 65℃, add preheated 3,3'-dichloro-4,4'-diaminodiphenylmethane, stir at 600 rpm for 5 min; then degas under -0.095 MPa vacuum for 15 min.

[0104] 5. Casting and molding: Pour the degassed mixture into a roller mold preheated to 120°C, and demold after curing for 20 minutes.

[0105] 6. Post-curing: Heat to 100℃ at a rate of 0.5℃ / min and hold for 11 hours to obtain fireproof elevator roller material.

[0106] Example 2: Raw material formulation: 100 parts of polyester-type polyurethane prepolymer (NCO mass fraction 4.2%); 12.0 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane ( (Molar ratio of 0.90); 8 parts of the first flame-retardant functional unit; 20 parts of the second flame-retardant functional unit.

[0107] The remaining preparation steps and process parameters are the same as in Example 1.

[0108] Example 3: Raw material formulation: 100 parts of polyether-type polyurethane prepolymer (NCO mass fraction 3.8%); 10.9 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane ( (Molar ratio of 0.92); 12 parts of the first flame-retardant functional unit; 15 parts of the second flame-retardant functional unit.

[0109] The remaining preparation steps and process parameters are the same as in Example 1.

[0110] Comparative Example 1 The raw material formula is exactly the same as that in Example 1.

[0111] Preparation process: The first flame retardant functional unit, the second flame retardant functional unit and the polyester polyurethane prepolymer were added to the reactor at one time and dispersed at 80°C and 1000 rpm for 40 min; the subsequent degassing, casting and post-curing steps were the same as in Example 1.

[0112] Comparative Example 2 Raw material formulation: 100 parts of polyester-type polyurethane prepolymer (NCO mass fraction 4.2%); 12.0 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane ( (Molar ratio of 0.90); 12 parts of unmodified submicron-sized melamine polyphosphate; 16 parts of unmodified micron-sized aluminum diethylphosphonate.

[0113] The remaining preparation steps and process parameters are the same as in Example 1.

[0114] Comparative Example 3 Raw material formulation: 100 parts of polyester-type polyurethane prepolymer (NCO mass fraction 4.2%); 12.0 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane ( (Molar ratio of 0.90); 12 parts of submicron-sized melamine polyphosphate modified with γ-glycidoxypropyltrimethoxysilane; 16 parts of unmodified micron-sized aluminum diethylphosphonate.

[0115] The remaining preparation steps and process parameters are the same as in Example 1.

[0116] Comparative Example 4 Raw material formulation: 100 parts of polyester-type polyurethane prepolymer (NCO mass fraction 4.2%); 12.0 parts of 3,3'-dichloro-4,4'-diaminodiphenylmethane ( The composition of the product is as follows: (molar ratio 0.90); 12 parts of unmodified submicron-sized melamine polyphosphate; 16 parts of unmodified micron-sized aluminum diethylphosphonate; and 2 parts of fumed silica thickener.

[0117] The preparation process uses a one-pot mixing method, and the remaining degassing, pouring, and post-curing steps are the same as in Example 1.

[0118] Performance testing methods and results Test methods 1. Flame retardant performance: According to the UL94 vertical burning test standard, a 3.2mm thick sample strip was used for testing, and the flame retardant rating and dripping condition were recorded.

[0119] 2. Mechanical properties: Tensile strength and elongation at break are tested according to GB / T 528 standard; abrasion loss is tested according to DIN53516 standard; Shore D hardness is tested according to GB / T 531.1 standard.

[0120] 3. Uniformity of flame retardant components: The surface distribution of phosphorus in the radial cross section of the fireproof elevator roller material was tested using an electron probe microanalyzer. The test parameters were set as follows: accelerating voltage 15kV, beam spot size 5μm, and plane scanning step size 10μm. The coefficient of variation of surface distribution (standard deviation / arithmetic mean × 100%) was calculated. The average phosphorus concentration in the surface layer (0.5mm depth range from the outer surface) and the geometric center region (circular range with a diameter of 2mm centered on the geometric center of the cross section) were tested respectively. The relative difference in phosphorus concentration between the surface and the center was calculated as (|average phosphorus concentration in the surface layer - average phosphorus concentration in the geometric center region| / average concentration of the cross section × 100%).

[0121] 4. Inter-batch stability: Five batches of samples were prepared continuously with the same formulation, and the relative standard deviation (RSD) of tensile strength was used to characterize the degree of performance dispersion between batches.

[0122] Test Results Results Explanation 1. All indicators of Examples 1 to 3 meet the scope defined in this application. The flame retardant performance stably reaches the UL94V-0 rating without melt dripping, while also exhibiting high tensile strength, high elongation at break, low abrasion loss, and low batch-to-batch performance dispersion. Examples 1 and 2 use a polyester polyurethane matrix, and Example 3 uses a polyether polyurethane matrix, all of which achieve excellent radial flame retardant component uniformity in fire-resistant elevator roller materials, demonstrating the good adaptability and universality of the process in this application.

[0123] 2. Comparison of Example 1 and Comparative Example 1 shows that by adopting a sequential stepwise dispersion process that first disperses submicron-level flame-retardant units and then adds micron-level flame-retardant units, the coefficient of variation of phosphorus surface distribution decreased from 27.6% to 13.5%, the relative difference of surface and core phosphorus concentration decreased from 18.5% to 7.3%, the flame retardant rating increased from V-2 to V-0, and the batch-to-batch relative standard deviation of tensile strength decreased from 16.3% to 5.1%. This demonstrates that sequential stepwise dispersion is a core technical means to improve the uniformity of radial flame-retardant element distribution in fireproof elevator roller materials and stabilize the performance of batch products.

[0124] 3. Comparison of Example 1 with Comparative Examples 2 and 3 shows that when only a single material in the two types of flame-retardant functional units is modified with silane, or when no silane modification is performed at all, it is impossible to rely on chemical bonds to bind the material to settle. The interfacial bonding strength and flame-retardant uniformity of the fireproof elevator roller material are both worse. Only when the first flame-retardant functional unit and the second flame-retardant functional unit are matched with epoxy-type and amino-type organosilicon modifying reagents, respectively, and the two undergo in-situ ring-opening addition to form a covalent bridging structure, can a synergistic effect be produced, and the mechanical properties and anti-settling ability of the material be improved simultaneously.

[0125] 4. As can be seen from the comparison between Example 1 and Comparative Example 4, the existing solution of adding fumed silica to thicken and inhibit sedimentation can slightly reduce the degree of stratification of flame retardant filler, but it will deteriorate the elongation at break and wear resistance of polyurethane material. However, this application does not require the addition of thickening agents. It relies on the dual mechanism of particle thixotropic network and covalent crosslinking to inhibit sedimentation, and takes into account both flame retardant uniformity and mechanical properties. Its comprehensive performance is better than the traditional thickening process.

[0126] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A process for preparing fireproof elevator roller material, characterized in that, A system for preparing fireproof elevator roller materials, the system comprising a reaction vessel, wherein the process includes: The first flame-retardant functional unit and the polyurethane prepolymer are added to the reactor and mixed under the first dispersion condition to obtain a premixed slurry; the first flame-retardant functional unit is a submicron flame-retardant filler modified with a silane coupling agent. A second flame-retardant functional unit is added to the premixed slurry, and the mixture is carried out under a second dispersion condition. The first active group carried on the surface modification layer of the first flame-retardant functional unit reacts chemically with the second active group carried on the surface modification layer of the second flame-retardant functional unit to form a covalent bridging structure between the first flame-retardant functional unit and the second flame-retardant functional unit, thereby obtaining a modified composite slurry. The second flame-retardant functional unit is a micron-sized flame-retardant filler modified with a silane coupling agent. A curing agent is added to the modified composite slurry, and the mixture is then subjected to degassing, casting, and post-curing treatments to obtain a fireproof elevator roller material.

2. The manufacturing process of the fireproof elevator roller material as described in claim 1, characterized in that, The curing agent is 3,3'-dichloro-4,4'-diaminodiphenylmethane; the amount of the curing agent used is based on the isocyanate content of the polyurethane prepolymer according to... The molar ratio was determined to be between 0.85 and 0.

95.

3. The manufacturing process of the fireproof elevator roller material as described in claim 1, characterized in that, The fireproof elevator roller material preparation system includes a wet stirring mill; the preparation method of the first flame-retardant functional unit includes: Melamine polyphosphate and zirconia grinding beads with a diameter of 0.3 mm to 0.5 mm are added to the wet stirred mill at a mass ratio of 1:8 to 1:

12. Deionized water is used as the grinding medium, and the mill is circulated and ground at a speed of 2000 rpm to 3000 rpm for 8 h to 16 h to obtain a grinding slurry. The median particle size D50 of the melamine polyphosphate in the grinding slurry after grinding is less than or equal to 500 nm, and the particle size D90 is less than or equal to 800 nm. γ-glycidyl etheroxypropyltrimethoxysilane is added to the grinding slurry at 1% to 3% of the mass of the melamine polyphosphate, and the mixture is stirred and reacted at 60°C to 80°C for 2 to 4 hours. The material after the reaction is completed is then spray-dried to obtain the first flame-retardant functional unit.

4. The manufacturing process of the fireproof elevator roller material as described in claim 1, characterized in that, The first flame-retardant functional unit is a submicron-sized melamine polyphosphate modified with γ-glycidoxypropyltrimethoxysilane, the median particle size D50 of the first flame-retardant functional unit is 200 nm to 500 nm, and the modification mass of the γ-glycidoxypropyltrimethoxysilane is 1% to 3% of the mass of the submicron-sized melamine polyphosphate; the second flame-retardant functional unit is a micron-sized aluminum diethylphosphinate modified with γ-aminopropyltriethoxysilane, the median particle size D50 of the second flame-retardant functional unit is 3 μm to 8 μm, and the modification mass of the γ-aminopropyltriethoxysilane is 0.5% to 1.5% of the mass of the micron-sized aluminum diethylphosphinate.

5. The manufacturing process of the fireproof elevator roller material as described in claim 1, characterized in that, The reactor includes a dispersion plate; the first dispersion conditions are a processing temperature of 50°C to 80°C, a stirring speed of 500 rpm to 800 rpm, and a mixing time of 15 min to 30 min; the second dispersion conditions are a processing temperature of 80°C to 100°C, a stirring speed of 800 rpm to 1200 rpm, and a mixing time of 20 min to 40 min.

6. The manufacturing process of the fireproof elevator roller material as described in claim 1, characterized in that, The reactor is equipped with a stirring shaft, and the stirring shaft is fitted with a torque sensor; the mixing under the first dispersion condition to obtain a premixed slurry includes: Torque signals are continuously acquired in real time using the torque sensor. The apparent viscosity of the slurry is obtained based on the torque signal; When the apparent viscosity of the slurry meets the preset qualified conditions, the pre-dispersion process is deemed qualified, and the premixed slurry is obtained.

7. The manufacturing process of the fireproof elevator roller material as described in claim 6, characterized in that, The preset qualification condition is that the apparent viscosity of the slurry corresponding to three consecutive sampling points is in the range of 800 mPa•s to 1600 mPa•s, and the fluctuation range of the apparent viscosity of the slurry corresponding to the three consecutive sampling points is less than or equal to 8% of the average value of the apparent viscosity of the slurry corresponding to the three consecutive sampling points.

8. The manufacturing process of the fireproof elevator roller material as described in claim 5, characterized in that, In the processing environment corresponding to the second dispersion condition, the epoxy groups carried by the surface modification layer of the first flame retardant functional unit undergo a ring-opening addition reaction with the primary amine carried by the surface modification layer of the second flame retardant functional unit to generate a β-hydroxy secondary amine bridging structure.

9. A fireproof elevator roller material, characterized in that, The fireproof elevator roller material is prepared by the fireproof elevator roller material preparation process described in any one of claims 1 to 8.

10. The fireproof elevator roller material as described in claim 9, characterized in that, The coefficient of variation of the flame-retardant characteristic element phosphorus in the fireproof elevator roller material along the radial cross section of the fireproof elevator roller material is less than or equal to 18%, and the concentration difference of the flame-retardant characteristic element phosphorus between the surface layer and the geometric center region of the fireproof elevator roller material is less than or equal to 10%.